Public health preparedness for pandemic influenza in Riley County, Kansas - Orr, JAON (My University, 2014)
Influenza viruses are constantly changing, which requires on-going characterization to provide early identification of emerging strains with pandemic potential. A close second to surveillance in prioritization is the ability of a public health system to respond to a developing pandemic. This report provides a detailed report on specific capabilities and capacities in public health preparedness within Riley County. The capabilities, capacities, and assessments within this report are in the context of an influenza pandemic. A variety of sometimes overlapping emergency standards, response capacities, and evaluation tools are in use within the nation. When appropriately used, these standards and measures can provide key insight across the nation into the strengths and weaknesses of the local public health system. Riley County’s recent local public health system assessment acknowledged a strength in disease identification, epidemiology, and investigation. Additionally, local emergency response agencies have shown great capabilities and capacities in preparing for and responding to daily emergencies. Information sharing, emergency operations coordination, and public information and warning capabilities recently received a favorable evaluation. The broader Riley County public health system, however, may be much less prepared and capable than those commonly identified as core emergency response agencies (police, fire, emergency medical services, and emergency management). Interagency communication and coordination are especially in need of development. If the local public health system is unable to respond as necessary to a complex public health emergency, such as an influenza pandemic, the local infrastructure may fail. Well-developed public health preparedness in advance of these public health emergencies are key to the success of the jurisdiction. This report summarizes observations of local public health agencies, some past agency responses, and some assessment of agency preparedness with a brief assessment on Riley County’s potential vulnerability to an influenza pandemic. This paper summarizes recommendations to: (1) develop a public health vulnerability analysis addendum to Riley County’s Hazard Analysis, (2) complete the systematic review developed herein, (3) evaluate the Riley County Health Department Public Health Emergency Preparedness program with available standards and measures, and (4) pursue medical surge planning with key stakeholders.
Keywords: Preparedness; Public health assessment; Influenza virus; Public Health (0573)